PENERAPAN MODEL PENEMUAN TERBIMBING DENGAN TEKNIK SCAFOOLDING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X MIA 4 MAN 1 PALU PADA MATERI FUNGSI: Aplication Of The Guided Discovery Model With The Scafoolding Technique To Imprive The Learning Outcomes Of Class X MIA 4 MAN 1 Palu Sudents On Functional Material - Dg. Sute, Hijrah Nur; Sukayasa; Rizal, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to describe the application of the guided discovery learning model with the Scaffolding technique in improving the students' abilities of class X MIA 4 MAN 1 Palu in the function material. This type of research is Classroom Action Research (CAR) and the design uses the Kemmis and Mc. Taggart, with its stages namely planning, action and observation and reflection. The subjects of this study were 17 students of class X MIA 4 MAN 1 Palu who were registered in the 2019/2020 school year and three students were selected as informants. This research was conducted in two cycles. Based on the results of the final action test, the percentage of students 'classical learning completeness in the first cycle was 73.33% and the percentage of students' classical learning completeness in the second cycle was 93.75%, while the results of teacher and student observations in the first cycle were in the good category and at cycle II is in the very good category. Based on the results of the study, it can be concluded that learning by applying the guided discovery learning model can improve the ability of class X MAN 1 Palu students on the function material by following the stages (1) stimulation: providing an explanation to students about the inverse function material contained in the LKPD. (2) problem formulation: directing students to find their own inverse function material by asking students to observe and identify the problems contained in the LKPD and make hypotheses. (3) data collection: students are asked to find references related to the inverse function material, then write down the information contained in the given problem carefully. (4) data processing: students process the data that has been collected by discussing the process used to find problems in the LKPD. (5) verification: students are asked to formulate conclusions and then match them with the formulation of the problem given whether the formulation of the conclusions made answers the given problem and whether the results obtained are in accordance with the hypotheses made have been proven or not. and (6) generalization: involving students in class discussions and concluding the material that has been studied.